RTHP-37. RE-IRRADIATION OF GLIOMATOSIS CEREBRI WITH WHOLE BRAIN PULSED REDUCED DOSE RATE RE-IRRADIATION. (11th November 2019) - Burr, Adam; Harari, Colin; Ian Robins, H; Howard, Steven
Abstract: BACKGROUND: Gliomatosis cerebri was removed from the 2016 WHO classification but the clinical problem of gliomatosis remains. For many of these patients, re-irradiation of the whole brain may be the only option. We have employed pulsed reduced dose rate (PRDR) radiation therapy to limit the toxicity of whole brain re-irradiation in this patient population. METHODS: Consecutive patients were identified from an institutional database of patients treated with PRDR radiation to the whole brain between 2001 and 2016. Patients were treated by delivering a 20 cGy pulse of radiation every 3 minutes to opposed lateral fields with custom blocks using 6 MV photons, delivering radiation at an effective dose rate of 6.67 cGy/minute. RESULTS: A total of sixteen patients were identified who underwent re-treated with WBRT. The median age was 45 (28–66) with a median KPS of 80 (range 60–100). 15 of 16 patients had high grade gliomas. The most common dose was 30 Gy in 15 fractions (range 24–41.4 Gy), giving a median total dose of 90.75 Gy (range 61.4–100.8 Gy). Median overall survival from re-irradiation was 3.8 months (range 0.1–17.0 months) and overall survival from first progression was 11.2 months. 25% of patients survived over 6 months following treatment and the overall response rate was 25% (3 PRs, 1 stable). No grade 4 or grade 5 toxicities were attributable to pulsed reduced dose rate radiation therapy. CONCLUSIONS: PRDR radiation therapy provides a potential therapeutic intervention for progressive gliomatosis cerebri, providing a treatment option that can be implemented where no trial is available. As survival is short, these results will assist in counseling patients in considering re-irradiation versus supportive care.